Strategic Restructuring and Outsourcing: The Effect of Mergers and Acquisitions and LBOs on Building Firm Skills and Capabilities - Lei, David; Hitt, Michael A. (Journal of Management, 1995)
A conceptual framework examining the relationship between corporate restructuring and outsourcing of key value-adding activities to external suppliers and partners is presented. The model proposes that the restructuring process serves as a catalyst to a series of complex changes within the firm that make outsourcing an attractive alternative to internal investments in the development of new skills and capabilities. High levels of merger and acquisition activity, as well as leveraged buy-outs (LBOs), are expected to produce a diminished resource base for organizational learning and technology development. Continued reliance on outsourcing, in turn, can potentially “lock out” the firm from participating in future technologies and new industries.